25 Years of Cell Cycle Research: What's Ahead?. (October 2016) - Gutierrez, Crisanto
Abstract : We have reached 25 years since the first molecular approaches to plant cell cycle. Fortunately, we have witnessed an enormous advance in this field that has benefited from using complementary approaches including molecular, cellular, genetic and genomic resources. These studies have also branched and demonstrated the functional relevance of cell cycle regulators for virtually every aspect of plant life. The question is – where are we heading? I review here the latest developments in the field and briefly elaborate on how new technological advances should contribute to novel approaches that will benefit the plant cell cycle field. Understanding how the cell division cycle is integrated at the organismal level is perhaps one of the major challenges. Trends: Research carried out mainly over the past 25 years has led to a detailed understanding of plant cell cycle at the physiological, cellular, molecular, genetic, and genomic levels. Many aspects of plant life, including formative cell divisions during organogenesis, the exit to differentiation, chromatin and epigenetics, metabolism and stem cell potential, circadian clock, and innate immunity, among others, impinge or depend directly on cell cycle regulators. Future challenges aim at obtaining an integrative understanding of cell proliferation in the whole plant. Recent advances in next-generation sequencing and single-cell omics, sophisticated imaging, and cell type-specific genome editing are among the novel approaches that should contribute to solve major questions on cell cycle research in model and crop species.